ANALISIS DESKRIPTIF RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFIBILITAS PADA PT MUSTIKA RATU TBK PERIODE 2020-2024 - Nabila Putri Aulia; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the financial performance of PT Mustika Ratu Tbk during the period 2020–2024 using financial ratio analysis, including liquidity, solvency, and profitability ratios. The research method used is descriptive quantitative with secondary data in the form of annual financial statements obtained from the company’s official website and the Indonesia Stock Exchange. The data analysis technique was carried out by calculating Current Ratio (CR), Quick Ratio (QR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Return on Equity (ROE). The results show that the company’s liquidity ratios are in good condition despite a declining trend, indicating that the company is still capable of meeting its short-term obligations. The solvency ratios indicate a relatively safe condition, although there is a tendency for increased use of debt in the company’s capital structure. Meanwhile, profitability ratios show poor performance with negative values in most of the research period, although there are indications of improvement in 2024. Overall, PT Mustika Ratu Tbk demonstrates strong liquidity and solvency conditions but has not been able to optimize its profitability performance. This study is expected to provide useful information for company management and investors in decision-making and serve as a reference for future research.